The Influence of Omnichannel Retailing, Customer Engagement, Customer Satisfaction, and Technology Acceptance Models on Customer Retention: An Alfagift Case Study - Maria Ariany; Ronny Samsul Bahri (Green Publisher Indonesia, 2025)
This study analyzes the influence of omnichannel retailing, customer engagement, customer satisfaction, and the technology acceptance model on customer retention among Alfagift app users. Despite the growing role of omnichannel strategies in digital retail, a significant research gap persists in Indonesia regarding their effects through engagement and satisfaction mediation, as well as technology acceptance moderation. Employing a quantitative approach with PLS-SEM (Structural Equation Modeling) analysis version 4.0.9.9, the study involved 300 active Grabmart Alfagift users who regularly utilize the platform. Results show that omnichannel retailing lacks direct impact on retention (β = 0.049, p > 0.05) but significantly affects it through engagement (β = 0.256, p = 0.001) and satisfaction (β = 0.231, p = 0.010) mediation. The technology acceptance model strengthens this relationship considerably. Theoretically, this research confirms the crucial mediating role in the customer retention process; practically, Alfagift should enhance personalized engagement strategies, improve app usability and functionality, and develop seamless offline-online integration to boost customer retention effectively and maintain competitive advantage in the digital retail landscape.